Antioxidant of n-hexane, ethyl acetate and methanol extracts of Padina sp with DPPH method. Issue 1 (July 2021) - Akbar, A; Soekamto, N H; Firdaus,; Bahrun,
Abstract: Padina sp. is seaweed which has high abundance in Indonesian waters, but the utilization of bioactive compounds is not yet optimal. This research intends to test the antioxidant activity of the secondary metabolites of Padina sp . in South Sulawesi waters. The extraction process uses a multilevel maceration method with n-hexane, ethyl acetate and methanol solvents, then followed by concentrating/drying the sample using the evaporation method. The extract obtained was then tested for phytochemistry, determined the levels of flavonoids and phenolics, and tested for antioxidant activity using DPPH method. The results of this research indicate that the extracts of n-hexane, ethyl acetate and methanol from Padina sp . contains flavonoids and phenolics with levels 103.0435; 124.5109; 111.7391 mg QE/g sample and 1.1504; 7.1289; 3.6325 mg GAE/g sample, respectively. n-hexane, ethyl acetate and methanol extracts of Padina sp . has antioxidant activity with IC50 values 117.3622; 115.7171; 116.8350 ppm, respectively. The IC50 value of n-hexane, ethyl acetate and methanol extracts of Padina sp .is in the medium category for antioxidant activity.